'Is global warming affecting the weather?' Evidence for increased attribution beliefs among coastal versus inland US residents. Issue 1 (2nd January 2020) - Cutler, Matthew John; Marlon, Jennifer; Howe, Peter; Leiserowitz, Anthony
ABSTRACT: Increasingly, researchers studying public beliefs about global warming have turned to the question of whether individuals have begun to perceive changes to their local climate conditions and to what extent they attribute these changes to the phenomenon of global warming. Perceptions of particular types of extreme events, i.e. extreme heat and droughts, have attracted the most attention, whereas the possible effects of place (such as proximity to coastal areas vulnerable to sea-level rise) on public beliefs about the link between changes to weather patterns and global warming have been largely neglected. This study matches geo-located responses to a nationally representative survey of US residents with climate extremes data in order to investigate the social and physical factors shaping public views about the links between global warming and extreme weather. Specifically, regional-level Climate Extremes Indices (CEI) are modelled together with individual-level socio-demographic characteristics and an indicator of coastal residence to test whether the incidence of extreme events and proximity to the coasts, net of social and economic factors, correspond to increased perceptions that global warming has affected the weather. Results indicate that coastal shoreline county residence significantly predicts individuals' beliefs about the extent to which global warming is affecting the weather.